Los santuarios novohispanos y las imágenes “peregrinas” entre historia e imaginario - Moro, Raffaele (El Colegio de México, A.C., 2017)
Religious practices in New Spain were strongly characterized by devotion towards miraculous images in shrines. This article studies the role played by petitioners  and “pilgrim” images (the duplicates normally carried by pilgrims along with their “questuas” of alms) in the diffusion of the cult of these images starting in the first half of the 17th Century, a subject that has gone unaddressed in the historiography until now. After offering a historical synthesis of pilgrimages to Marian shrines, the article reflects on their status in the society and imagination of New Spain. The hypothesis it proposes is that pilgrim images were a sort of double of the shrines’ images, not mere copies.